Synthesis, Antimicrobial Activity, and Photocatalytic Performance of Ce Doped SnO2 Nanoparticles - Bhawna,; Choudhary, Ashish Kumar; Gupta, Akanksha; Kumar, Sanjeev; Kumar, Pramod; Singh, R. P.; Singh, Prashant; Kumar, Vinod (Frontiers in Nanotechnology, 2020)
This work represented the synthesis of Ce doped SnO2 nanoparticles by a wet chemical method and was characterized by various characterization techniques. PXRD confirmed the presence of the rutile phase for Ce doped SnO2 nanoparticles. SEM image and elemental mapping showed agglomerated irregular shaped particles and uniform distribution of 5% Ce ions within the SnO2 lattice, respectively. Ce doped SnO2 nanoparticles showed antimicrobial activity against E. coli and prevented the growth of bacteria. The nanoparticles were found photocatalytic active and photocatalytic behavior was elucidated by the degradation of Malachite Green dye under UV light irradiation.